Principles of Buyer’s Responsibility on Bid and Run Actions in Online Auction Buying and Selling Practices - Pesulima, Theresia Louize (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The development of the internet causes the practice of buying and selling auctions can not only be done conventionally but can also be done online, one of which is by using Instagram media. This online auction transaction not only provides benefits and convenience for consumers but also has weaknesses and in fact in online auction buying and selling transactions , losses can not only be experienced by consumers, but business actors can also experience losses due to non-fulfillment of achievements that should be done by consumers. One of the consumer actions that harm business actors is Bid an Run in the practice of buying and selling online auctions on Instagram social media.Purposes of the Research: The purpose of this article is to find out the application of the principle of buyer’s responsibility for bid and run actions as a form of legal protection for business actors.Methods of the Research: The research method used in this research is normative juridical or known as legal research which is carried out by studying and analyzing the substance of laws and regulations on the subject matter or legal issues in consistency with existing legal principles.Results of the Research: The results show that Legal liability for buyers who in bad faith deliberately do not pay or take bid and run actions can be sued based on Article 1243 of the Civil Code, Article 21 paragraph (2) letter a and paragraph (4) of the ITE Law, and Article 6 letter a and b of the Consumer Law, as well as electronic agreements that have been agreed between business actors (auction account owners) and consumers (auction bidders). Business actors in this case can also sanction directly to consumers who have committed violations by blocking the consumer's account and being blacklisted so that consumers cannot bid with auction business actors anywhere.